OPTIMASI KONSENTRASI TEMULAWAK DAN WAKTU PERENDAMAN SEBAGAI PEREDUKSI FORMALIN PADA TAHU MENGGUNAKAN RESPONSE SURFACE METHODOLOGY - Gumilar, Anggi; Dewi, Mira Andam; Salsabila, Nabila Hafna (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Tofu is a food product that contains high water which causes the shelf life of tofu to be short. Some manufacturers add preservatives to extend its shelf life. However, some rogue manufacturers add prohibited preservatives such as formalin. Formalin reduction can be done using Curcuma xanthorrhiza, which can reduce formalin through saponification mechanism. This research aims to determine the optimal conditions for formalin reduction using curcuma. Tofu samples that have been contacted with formalin were treated by immersion with a solution of curcuma, then reacted with Schiff’s reagent and measured by spectrophotometer UV-Visible at a maximum wavelength of 556 nm. Optimization was carried out using Response Surface Methodology (RSM) with Central Composite Design (CCD) method. Independent variables that were used in this optimization were concentration of curcuma and soaking time. Data analysis of reduced formalin content was carried out using Minitab version 19. RSM equation for optimization of concentration of curcuma (X1) and soaking time (X2) to obtain the maximum value of reduced formalin is y=19,63–1,70X1–0,368X2+0,2034X12+0,00954X22–0,0052X1X2. The optimization results of RSM showed that the optimal condition was at concentration of 8.53% v/v and immersion time of 51.21 minutes, with a predicted amount of reduced formalin of 23.90 µg/g (45,89%).